Economic productivity in Israel - Gaathon, A. L. (New York : Praeger [Published] in cooperation with the Bank of Israel, 1971)
The book is divided into six chapters: 1. Output 2. The Human Factor. 3. Capital Stock. 4.Factor Productivity. 5. Long-term Productivity 6. Postscripts: 1965-69
Includes in index.
Includes bibliographical references: p. 265-271.
rpm 24/01/2019
Loans
Keywords: Capital productivity; Labor productivity